Flea parasitism in wild mammals in the metropolitan region of Sorocaba, São Paulo, Brazil - Teixeira, Rodrigo Hidalgo Friciello [UNESP]; da Costa, André Luiz Mota [UNESP]; Gonzaga, Cassia Regina Ramos; Matos, Flora Nogueira; de Medeiros, Marina Alvarado; de Fátima Sallum Leandro, Shamira; Matheus, Ronnie Von; Bellotti, Maria Atalla; Lima, Beatriz Freitas; Sakamoto, Cláudio Alessandro Massamitsu; Barros, Luciano Antunes (Revista Brasileira de Medicina Veterinaria, 2023)
Fleas are eurixenous ectoparasites that can parasitize different species of warm-blooded animals, including humans, with the possibility of causing irritation and blood spoliation. They are vectors responsible for the transmission of numerous pathogens and have a wide geographical distribution, more frequently in warm regions. Domestic animals (dogs and cats) are preferred hosts, but parasitism can also occur in wild hosts, with a greater variety of parasitic species and strong interaction between these siphonapters and their hosts. During the period from January 2021 to June 2023, flea specimens were collected from wild animals coming from the metropolitan region of Sorocaba, São Paulo. Some of these animals were animals from the zoo’s own stock, which were diagnosed with parasitism during routine examinations and others were rescued from the natural environment and sent to the zoo. The flea specimens collected were packed in alcohol 700 GL and sent for microscopic diagnosis. Four groups were diagnosed at the specific level: Ctenocephalides felis, Rhopalopsyllus lutzi, R. lugrubis and Tunga penetrans, and two groups as unidentified species, belonging to the genera Rhopalopsyllus and Polygenis. The parasitized animals were all mammals, belonging to eleven different species, distributed in the Orders Carnivora, Didelphimorphia, Rodentia and Cingulata. Studies on the parasitofauna of wild animals contribute to a greater knowledge about the distribution of parasitic agents and their relationships with the host species.
Parasitismo por sifonápteros em mamíferos silvestres na região metropolitana de Sorocaba, São Paulo, Brasil
Keywords: ectoparasite; siphonaptera; zoological